2016
DOI: 10.1007/s11060-016-2111-3
|View full text |Cite
|
Sign up to set email alerts
|

A preclinical murine model for the early detection of radiation-induced brain injury using magnetic resonance imaging and behavioral tests for learning and memory: with applications for the evaluation of possible stem cell imaging agents and therapies

Abstract: Stem cell therapies are being developed for radiotherapy-induced brain injuries (RIBI). Magnetic resonance imaging (MRI) offers advantages for imaging transplanted stem cells. However, most MRI cell-tracking techniques employ superparamagnetic iron oxide particles (SPIOs), which are difficult to distinguish from hemorrhage. In current preclinical RIBI models, hemorrhage occurs concurrently with other injury markers. This makes the evaluation of the recruitment of transplanted SPIO-labeled stem cells to injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…, 27 (55%), investigate BBB disruption in rats [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] . In addition, eleven (22%) studies use mice [12] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , five involve rabbits [88] , [89] , [90] , [91] , [92] , two include dogs [93] , [94] , two describe monkeys [95] , [96] , one article studied the effects of RT on the BBB in sharks [97] and one in pigs [98] .…”
Section: Resultsmentioning
confidence: 99%
“…, 27 (55%), investigate BBB disruption in rats [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] . In addition, eleven (22%) studies use mice [12] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , five involve rabbits [88] , [89] , [90] , [91] , [92] , two include dogs [93] , [94] , two describe monkeys [95] , [96] , one article studied the effects of RT on the BBB in sharks [97] and one in pigs [98] .…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies exist that reported on the use of OCT to detect ARIED in mice [15]. Moreover, other studies used MRI to detect and monitor radiation-induced degenerative changes in articular cartilage and bone in rats [40], progression of radiation-induced necrosis and dose escalation limitations in mouse and rat brains respectively [41, 42], radiation-induced damage in mouse brains [4346] in xenografts in mice [47, 48], and radiation-induced lung damage in rabbits [49]. However, no studies have reported use of MRI to detect ARIED.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac MRI is used to evaluate cardiac function in preclinical models of heart disease. 87,88 MRI is particularly advantageous in studying the soft tissue anatomy: resolutions of 25 to 100 μm are achievable in preclinical animal studies of cancer, 89 brain injury, 90 and stem cells. 91 Advantages MRI is a powerful, noninvasive method for phenotypical characterization and therapeutic efficacy evaluation in animal models of disease used in preclinical research and drug discovery and development.…”
Section: Mri Modalitymentioning
confidence: 99%